Anxiety and Defense Mechanism as A Means of Constructing Psychological Thriller in Hawkinsâ€™ â€œThe Girl on The Trainâ€ (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
The topic of this study is Anxiety and Defense Mechanism as A Means of Constructing Psychological Thriller in Hawkins’ The Girl on the Train. The objectives of this study are to describe how anxiety and defense mechanism are described in Hawkins’ The Girl on the Train and to explain how anxiety and defense mechanism construct psychological thriller as represented in Hawkins’ The Girl on the Train. The object of the study is a novel entitled The Girl on the Train written by Paula Hawkins. This study is descriptive qualitative study by applying Freudian psychoanalytic theory. The data of the study were collected by reading, identifying, interpreting, and inventorying citations from the novel. Further, the data were analyzed based on Freudian psychoanalytic theory by describing anxiety and defense mechanism described in the novel. The data were also analysed by explaining how anxiety and defense mechanism construct psychological thriller. The results show there are three kinds of anxiety and six kinds of defense mechanism. Moreover, the results prove that those anxieties and defense mechanisms become a means of constructing psychological thriller since they make the characters suffer from psychological problem and become unreliable narrator, create plot twist, and make the novel become thrilling. Keywords: Psychological thriller, Freudian psychoanalysis, Anxiety, Defense Mechanism